Comparison between paramagnetic and CD71 magnetic activated cell sorting of fetal nucleated red blood cells from the maternal blood. Issue 9 (25th June 2020) - Nemescu, Dragos; Constantinescu, Daniela; Gorduza, Vlad; Carauleanu, Alexandru; Caba, Lavinia; Navolan, Dan Bogdan
Abstract: Background: Fetal nucleated red blood cells (NRBC) from maternal circulation are rare events but can be enriched and used to evaluate the genetics of the fetus. We compared two simplified selection methods of the fetal cells from the maternal blood. Methods: We isolated fetal cells from maternal blood through double‐density gradient centrifugation followed either by magnetic cell selection, based on the paramagnetic proprieties of the NRBC hemoglobin, converted to methemoglobin, or by a positive magnetic‐activated cell sorting (MACS) enrichment, using anti‐CD71 monoclonal antibodies. Finally, the cells were identified through fluorescence in situ hybridization (FISH) with specific chromosome X and Y probes. Results: We processed 10 mL of peripheral blood samples from 27 pregnant women with singleton normal male fetuses. Hemoglobin‐based enrichment isolated significantly more NRBCs: 29.7 × 10 4 cells than anti‐CD71 MACS: 10.1 × 10 4 cells ( P  < .001). The FISH analysis found at least one XY cell in 81.5% and 61.5% of cases, respectively, for paramagnetic and anti‐CD71 selection. Also, the average number of XY cells identified through paramagnetic selection was 5.09 ± 2.5, significantly higher than those observed through CD71 sorting: 3.38 ± 1.7 cells (average ± SE) ( P  = .03). Conclusion: The combination of density gradient centrifugation with paramagnetic selection has the advantage of simplicity and achieves a minimal manipulation and treatment of cells. It yields an increased number of NRBCs and FISH confirmed fetal cells, compared to the anti‐CD71 sorting.